2021
DOI: 10.1111/jfpe.13746
|View full text |Cite
|
Sign up to set email alerts
|

Pilot‐scale hydraulic‐pressure extraction of Sukari date honey (Phoenix dactylifera L.) to enhance resource efficiency: Effects of processing parameters on bioactive compounds and physicochemical quality

Abstract: The present study explored the hydraulic pressure process as an alternative process to the conventional extraction of date honey. In this regard, response surface methodology (RSM) and central composite design (CCD) were utilized as process optimization tools to achieve the highest yield and efficiency. Independent processing parameters were temperature (50–60°C) and pressure (4–12 bar). Moreover, the effect of optimum conditions on the quality and active compounds of date honey were studied. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Hussain, Farooq [ 35 ] revealed that the total sugar of Sukari variety date fruit was 78.5%. As Al‐Hilphy, Al‐Fekaiki [ 15 ] indicated, the moisture, fat, protein, ash, fiber, and sugar of the Sukari variety date were 12.598, 1.681, 2.520, 0.241, 6.86, and 78.01%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hussain, Farooq [ 35 ] revealed that the total sugar of Sukari variety date fruit was 78.5%. As Al‐Hilphy, Al‐Fekaiki [ 15 ] indicated, the moisture, fat, protein, ash, fiber, and sugar of the Sukari variety date were 12.598, 1.681, 2.520, 0.241, 6.86, and 78.01%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The results are close to those of Farahnaky, Mardani [ 39 ], who confirmed that the moisture content of date syrup was 24.07%. Al‐Hilphy, Al‐Fekaiki [ 15 ] found that the moisture content of date syrup extracted by heat (the traditional method) was 31.03%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations